2019
DOI: 10.1111/acel.13058
|View full text |Cite
|
Sign up to set email alerts
|

Osmolyte transporter expression is reduced in photoaged human skin: Implications for skin hydration in aging

Abstract: Aging is characterized by the deterioration of tissue structure and function. In skin, environmental factors, for example, ultraviolet radiation (UVR), can accelerate the effects of aging such as decline in barrier function and subsequent loss of hydration. Water homeostasis is vital for all cellular functions and it is known that organic osmolyte transport is critical to this process. Therefore, we hypothesized that as we age, these tightly controlled physiological mechanisms become disrupted, possibly due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…nih.gov/gene/). However, based on the immunohistochemical study, the taurine transporter is highly expressed in epidermis, but not dermis, among the skin layers, 39,40 indicating that the location of the taurine transporter may be involved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…nih.gov/gene/). However, based on the immunohistochemical study, the taurine transporter is highly expressed in epidermis, but not dermis, among the skin layers, 39,40 indicating that the location of the taurine transporter may be involved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Inconsistently, the concentration of NMT in skin is low, while skin might averagely express the taurine transporter gene according to the database for gene expression (). However, based on the immunohistochemical study, the taurine transporter is highly expressed in epidermis, but not dermis, among the skin layers, , indicating that the location of the taurine transporter may be involved.…”
Section: Resultsmentioning
confidence: 99%
“…Human epidermal keratinocytes actively proliferate and differentiate to maintain the integrity of skin. However, keratinocytes have a finite lifespan and aged cells show reduced cell division and senescence phenotypes 60 . This sometimes makes it difficult for aged people to replenish the damaged regions of their skin 61 .…”
Section: Resultsmentioning
confidence: 99%
“…An in vivo study using taurine transporter knockout mice showed that epidermal taurine is involved in the photoprotection of skin (Rockel et al 2007 ). Recently, the study using human skin samples showed that epidermal keratinocytes possess osmolyte-mediated cell volume regulatory mechanisms, which is compromised in aging (Foster et al 2020 ). Furthermore, taurine has been shown to enhance the structure and function of tight junction in keratinocytes (El-Chami et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%